2012
DOI: 10.1001/archinternmed.2011.2174
|View full text |Cite
|
Sign up to set email alerts
|

Sitting Time and All-Cause Mortality Risk in 222 497 Australian Adults

Abstract: Prolonged sitting is a risk factor for all-cause mortality, independent of physical activity. Public health programs should focus on reducing sitting time in addition to increasing physical activity levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
488
3
13

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 756 publications
(543 citation statements)
references
References 34 publications
20
488
3
13
Order By: Relevance
“…This is important because low levels of physical activity and prolonged sitting time have been shown to be independent risk factors for all-cause mortality. [14][15][16] HEALÔ participants also achieved significant increases in fruit and vegetable consumption. Results from the 1995 Australian National Nutrition Survey and 2011-2012 Australian National Health Survey indicated that while 50% of people surveyed were eating two or more serves of fruit a day, only 20%-30% were eating four or more serves of vegetables.…”
Section: Behaviour Changementioning
confidence: 99%
“…This is important because low levels of physical activity and prolonged sitting time have been shown to be independent risk factors for all-cause mortality. [14][15][16] HEALÔ participants also achieved significant increases in fruit and vegetable consumption. Results from the 1995 Australian National Nutrition Survey and 2011-2012 Australian National Health Survey indicated that while 50% of people surveyed were eating two or more serves of fruit a day, only 20%-30% were eating four or more serves of vegetables.…”
Section: Behaviour Changementioning
confidence: 99%
“…[1][2][3][4][5][6][7] There are indications that not only is total sedentary time important, but also how this time is accumulated throughout the day. Previous studies have shown that frequent interruptions in sedentary time may be associated with beneficial health outcomes, 8,9 suggesting that breaking up sedentary time may offset the detrimental effects of high total sedentary time.…”
Section: Introductionmentioning
confidence: 99%
“…O rastreamento e a quantificação dos fatores de risco à saúde mental caracterizam-se como medidas importantes para a prevenção de danos a população idosa. Apesar de não ter sido observada associação entre CS e TMC no presente estudo, achados da literatura mostraram que o incremento do tempo despendido em atividades sedentárias aumenta o risco de morbimortalidade 8,[20][21][22][23] . Gastar tempo demasiadamente em comportamento sedentário leva a piores condições de saúde e mortalidade prematura 24 .…”
Section: Discussionunclassified
“…Ao relacionar o comportamento sedentário, a prática de atividade física e indicadores de mortalidade em idosos, percebe-se que o tempo adequado de prática de atividade física não elimina o risco de mortalidade decorrente do excesso de atividades sedentárias 8,18,22,27,28 . O estilo de vida moderno, caracterizado por elevado tempo livre em atividades sedentárias, está associado a maior isolamento social e, com isso, a aumento do risco de disfunção cognitiva e mental 29 .…”
Section: Discussionunclassified